A stroke mimicker following inferior alveolar nerve block: a case report - Hassan Muhammad Kamil; Singh Namkabir; Selvaraju Kalpana; Ngeow Wei Cheong (EDP Sciences, 2023)
Introduction: Local anesthesia administration albeit being the most common dental procedure is associated with complications that usually arise as a result of wrongly placed injections into local or distant sites. Here we present a case of an unexpected complication affecting the upper limb after dental anesthesia administration. Observation: A 26-year-old Malay female presented with the left upper extremity paralysis and paraesthesia following the administration of a local anesthesia block to the left inferior alveolar nerve, at a dental teaching center. The onset of the dental nerve block and left upper extremity weakness occurred and eventually subsided. As the provisional diagnosis was either a transient ischaemic attack or stroke, she was immediately referred to the Emergency Department. She was thoroughly assessed and monitored with the neurology team being consulted. Her vital signs remained stable and she showed no neurological deterioration throughout the observation period. She was discharged without further investigations after regaining full strength and sensation of her left upper extremity. The report tries to hypothesize the possible cause of this incident. Conclusion: This case highlights the importance of dentists being alert to possible effects of local anesthesia to regions beyond the head and neck area.